PUNCAK AGUNG TIGER TEMPLE IN BAYU VILLAGE SONGGON DISTRICT (HISTORY, STRUCTURE AND FUNCTIONS OF THE TEMPLE) - Ainun Najib Buchori; I kadek Yudiana; Mahfud; Sahru Romadhoni (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This research was conducted in Bayu Village, Songgon District. This study aims to determine: (1) The history of the Puncak Agung Macan Putih temple temple; (2) Structure of the Candi Puncak Agung Macan Putih Temple; (3) Functions of the Temple of Puncak Agung Macan Putih Temple. The steps used are: (1) Heuristic data collection (observation, interviews, study of documents); (2) Criticism of sources; (3) Interpretation; (4) Historiography (writing history). The subjects of this study were local leaders and elders who embrace Hinduism in Bayu Village, Songgon District. The result of this research is that the Candi Puncak Agung Macan Putih Temple was built in 2005-2007, which was proposed by Ida Bagus Alit. He is originally from Bali who seeks peace in the Rawa Bayu area. When doing meditation, he got an inspiration so that in that area there should be a temple. after that he asked permission from the caretaker of Rawa Bayu to build a temple here. After the elders and caretakers of Rawa Bayu agreed to Ida Bagus Alit's suggestion, he immediately returned to Bali to take the padmasana to be placed in Rawa Bayu. The structure of the Puncak Agung Macan Putih Temple uses the Eka Mandala concept, which means the unity of the upper and lower realms. The only building in the Puncak Agung Macan Putih Temple Temple is Padmasana. This is because the Puncak Agung Macan Putih Temple Temple is located on a mountainside and is quite far from residential areas so that it was built as simply as possible. The functions of the Puncak Agung Macan Putih Temple Temple include: (1) Religious functions: as a place to pray to Ida Sang Hyang Widhi and perform other religious rituals; (2) Educational function: as a place to study history for students because in Rawa Bayu there is a place and relics of Prabu Tawang Alun who was the King of Blambangan, and was the place where the Puputan Bayu war took place; (3) Social function: as a place to commemorate HARJABA because the Puncak Agung Macan Putih Temple temple is still in the same location as the Rawa Bayu tourist destination.